Analisis Pertanian Pada Subsektor Biofarmaka Di Kabupaten OKU Timur Sumatera Selatan - Ary Eko Prastya Putra; Andri Irawan; Fiana Laila (Jurnal Bakti Agribisnis, 2024)
In optimizing the source of agricultural analysis in the biopharmaceutical sub-sector of the East OKU of South Sumatra, it is necessary to analyze the economic potential of all sectors, especially the agricultural sector which is finally able to prepare regional development planning effectively and efficiently as capital in realizing regional development. The purpose of this analysis is to determine the superior potential of plants in the biopharmaceutical subsector and plant growth in the biopharmaceutical subsector. Data were taken from 20 sub-districts in East OKU and 17 districts in South Sumatra for analysis, the data analyzed was biopharmaceutical production data. The research method used is a secondary data method available in the form of publication or databese. The results for the Location Quotient analysis showed that the types of biopharmaceutical plants classified as base plants (superior) with an LQ value of > 1 were ginger with a value of 1.86, kencur with a value of 1.28. Meanwhile, for non-base plants (not superior) with an LQ value of < 1, namely turmeric 0.35 and galangal 0.39. The results of the Shift Share analysis in the 2018-2023 period show that all types of plants in the biopharmaceutical subsector experienced poor growth which resulted in a negative value (-). For ginger plants have a value of – 255,682, kencur plants have a value of – 624,529. Turmeric plants have a value of – 29,872, and galangal plants have a value of – 83,158.